2021
DOI: 10.1007/s00704-021-03828-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal trends of temperature extremes in Bangladesh under changing climate using multi-statistical techniques

Abstract: The rise in the frequency and magnitude of extreme temperature phenomena across the globe has led to the recurrent incidence of global climate hazards, which have had severe effects on socioeconomic development. The daily maximum and minimum temperature datasets of 27 sites in Bangladesh were used to detect spatiotemporal trends of temperature extreme over Bangladesh during 1980-2017 based on ten temperature extreme indices using multistatistical modeling namely linear regression, Pearson correlation coefficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 80 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…Future research might concentrate on how large-scale atmospheric circulations are connected to the increasing tendencies of MHWs, as revealed by some related studies [ 47 49 ]. Studies on heat waves in various countries and regions, including Portugal [ 50 ], the Middle East [ 51 ], Iran [ 52 ], Northeast China [ 53 ], Central Europe [ 54 ], Bangladesh [ 9 ], and the Sahel [ 55 ], have shown positive trends that are consistent with a warming of earth’s climate [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future research might concentrate on how large-scale atmospheric circulations are connected to the increasing tendencies of MHWs, as revealed by some related studies [ 47 49 ]. Studies on heat waves in various countries and regions, including Portugal [ 50 ], the Middle East [ 51 ], Iran [ 52 ], Northeast China [ 53 ], Central Europe [ 54 ], Bangladesh [ 9 ], and the Sahel [ 55 ], have shown positive trends that are consistent with a warming of earth’s climate [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trend analysis has been used to detect the impacts of climate change on precipitation, temperature, and evapotranspiration in the Kasem watershed. The Mann-Kendall test is a nonparametric test that does not require the data to follow normal distribution [51]:…”
Section: Trend Analysismentioning
confidence: 99%
“…It can directly or indirectly impact many aspects of society by potentially disrupting the normal natural balance and forcing the change of weather patterns [5]. Increasing temperature trends (warming), and other associated factors are threatening human existence, ecological communities, and socioeconomic development across the world [6]. The Intergovernmental Panel on Climate Change (IPCC) reported that the global mean temperature had risen (global warming) about 0.85 (±0.2) °C from 1880 to 2012 [1,7].…”
Section: Introductionmentioning
confidence: 99%